2018
DOI: 10.1371/journal.pone.0206344
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and implications of the dynamics of eosinophils in blood and in the infarcted myocardium after coronary reperfusion

Abstract: ObjectiveWe characterized the dynamics of eosinophils in blood and in the infarcted myocardium in patients and in a swine model of reperfused myocardial infarction (MI). The association of eosinophil dynamics with various outcomes was assessed.MethodsSerial eosinophil count and pre-discharge cardiac magnetic resonance were carried out in a prospective series of 620 patients with a first ST-elevation MI. In a swine model of reperfused MI, the dynamics of circulating eosinophils and their presence in the infarct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 32 publications
1
25
0
1
Order By: Relevance
“…Limited is known about sex differences in eosinophils in STEMI patients. Previous research studied eosinophil levels in 620 STEMI patients and observed an association between a decrease in eosinophils and higher risk of major adverse events 18 . However, analyses were not stratified by sex.…”
Section: Discussionmentioning
confidence: 99%
“…Limited is known about sex differences in eosinophils in STEMI patients. Previous research studied eosinophil levels in 620 STEMI patients and observed an association between a decrease in eosinophils and higher risk of major adverse events 18 . However, analyses were not stratified by sex.…”
Section: Discussionmentioning
confidence: 99%
“…A 2.5 × 15 mm over-the-wire angioplasty balloon was inflated to 6 atm immediately distal to the first diagonal branch and coronary artery occlusion was confirmed by contrast injection and by electrocardiographic ST-segment elevation. Additional details on our experimental models can be consulted elsewhere 14,25,26 .…”
Section: Methodsmentioning
confidence: 99%
“…After MI, inflammation is a physiological and necessary response that initiates repair. However, when out of control, this process can lead to unnecessary myocardial and microvascular damage [15,16]. Neutrophils, via aggregation and formation of neutrophil extracellular traps, decisively participate in MVO progression [17].…”
Section: Pathophysiologymentioning
confidence: 99%
“…In the field of biomarkers, an important and early rise in troponin is associated with more extensive MVO [20]. Regarding white blood cells, increases in innate immunity cell counts (neutrophils and monocytes) and decreases in adaptive-effector immunity cell counts (lymphocytes and eosinophils) are associated with MVO [15,16].…”
Section: Diagnostic Toolsmentioning
confidence: 99%